Poster Seruan Edukasi Vaksin Covid-19: Kajian Semiopragmatik - Saiyidinal Firdaus (Faculty of Engineering, Universitas Semarang, 2025)
In 2021, the Indonesian government, through the Ministry of Health, made efforts to promote the vaccination program to the public. Therefore, the government needed to explain various aspects related to the program, such as the definition of vaccines, the purpose of vaccination, how vaccines work, recommendations for the public, program achievements, and the age limits for vaccine recipients. The vaccination campaign messages delivered by the Indonesian government through the Ministry of Health were represented through verbal and non-verbal expressions on posters. The COVID-19 vaccination educational posters contain messages encapsulated in the relationship between signs and expressive utterances. Consequently, this study aims to identify and describe the conveyed meanings within the COVID-19 vaccination educational posters using Peirce's Semiotic approach and Searle's Pragmatic approach. This research adopts a qualitative methodology. Data were collected from the texts and images featured in the posters. These texts and images represent meanings that form signs in the categories of icon, index, and symbol (semiotics), as well as directive illocutionary acts in direct speech (pragmatics). The COVID-19 vaccination educational posters serve as a strategy for the government to encourage public willingness to get vaccinated. From a pragmatic interpretative perspective, the semiosis of the overall poster content is demonstrated through direct utterances with affective perlocutionary force.